REPRESENTATION OF THE RELATIONSHIP BETWEEN THE VICTIM AND THE OFFENDER IN THE GENERAL PART OF THE CRIMINAL CODE OF UKRAINE - Корягіна, Анжела Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the article reveals the issue of consolidating the characteristics of the relationship between the victim and the subject of the crime. The norms of the General Part of the Criminal Law Law are analyzed. Methods: analysis of the relationship between the victim and the subject of the crime, conducted on the basis of the general theoretical provisions of the science of criminology, psychology and criminal law, developed by leading domestic and foreign scientists. Results: determine the significance of fixing the signs of the relationship between the victim and the subject of the crime. Discussion: the analysis of the General Part of the Criminal Code of Ukraine concerning the fixing of the characteristics of the connection between the victim and the subject of the crime in its norms is underway. This article is devoted to the analysis of the General Part of the Criminal Code of Ukraine regarding the establishment of the norms of the relationship between the victim and the subject of the crime. As you know, the crime is the basis of criminal liability. Signs of the crime, including the characteristics that characterize the victim, if they are included in the composition, determine the conditions and limits of criminal and punitive. Analyzing the Criminal Code of Ukraine, we see that the victim does not include all the components of crimes that cause harm to a person, but only when there is a need to narrow the range of victims. But in practice, there are often problems both during qualification and when sentencing guilty persons for a crime committed as a result of unlawful behavior of the victim, for example, when deliberate causing bodily injuries occurred during a joint fight. In our opinion, these errors arise because insufficiently thoroughly analyzed the mechanism of such a crime. In order to prevent mistakes in qualification, it is necessary to comprehensively analyze the actual behavior of the victims, which is necessary to find out the effectiveness of criminal law in combating their anti-social behavior, as well as punishment in terms of strict compliance with the principle of individual victim guilty and to improve the current legislation. In order to investigate the place and functions of the relationship between the victim and the offender in criminal law, we have analyzed the norms of the General and Special Parts of the Criminal Code of Ukraine, which allows certain parts of the rules of the Special Part to be divided into those which prescribe the signs of "crimes of relationships" and those that imply responsibility for acts, which may be «crimes of intercourse». Certain aspects of the relationship between the victim and the subject of a crime have a criminal significance. Thus, in the General Part of the Criminal Code of Ukraine, they were reflected: 1) in the rules on the circumstances excluding the crime of the act (first of all, it concerns the necessary defense, imaginary defense, the detention of a person who committed a crime, physical or mental coercion); 2) in the rules on release from criminal responsibility (institutions of effective repentance, reconciliation of the guilty party with the victim); 3) in the rules on the imposition of punishment (circumstances that mitigate and aggravate the punishment).